THE RELATIONSHIP BEHAVIOR OF TYPE II DIABETES MELITUS CONTROL WITH PATIENTS' BLOOD GLUCOSE LEVELS IN THE WORKING AREA OF THE INDRAJAYA PUSKESMAS INDRAJAYA DISTRICT, PIDIE REGENCY - Rahmi, Ananda Fathur; Santi, Tahara Dilla; Azwar, Eddy (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Cases of type II Diabetes melitus (DM) in the working area of the Indrajaya Health Center, Pidie Regency, increased from 500 cases in 2017 to 533 cases in 2019. The increase in the number of cases is an indicator that the behavior of controlling type II DM is not optimal. The purpose of this study was to determine the relationship between type II DM control behavior and blood glucose levels in patients in the working area of the Indrajaya  Community Health Center, Indrajaya District. Method: This research is an analytic descriptive with a cross-sectional design. A sample of 66 patients was determined through the Random Sampling Technique. Data analysis used the Chi-Square test with SPSS version 20. Result: there is a relationship between physical activity (p value = 0.012), lifestyle (p value = 0.036), diet (p value = 0.002), and medication adherence (p value = 0.006) with blood glucose levels in DM patients and there is no relationship between smoking behavior (p value = 0.326) with blood glucose levels in DM patients. Recommendation: It is hoped that health workers can increase counseling to the community about preventing DM and encourage morning exercise with the community at least once a week.